1995
DOI: 10.1073/pnas.92.10.4422
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically critical nucleotide in domain 5 of a group II intron.

Abstract: (5) by binding to domain 1 (6) to activate domain 6 (7). Previous work (S. C. Boulanger, et aL, unpublished data) has identified sites that are important for D5 function, but that study could not provide a specific diagnosis for the functional defects of inactive variants. We have applied a trans assay by using a 36-nt D5 RNA that activates group II intron transcripts deleted for D5 (AD5; see Fig. 1) (7,9). Accurate hydrolysis at the 5' splice junction is the most efficient reaction, although branching and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 13 publications
4
97
0
Order By: Relevance
“…The catalytic core of the spliceosome consists of a highly structured RNA network formed between U2, U6, and U5 snRNAs and the sites of chemistry in the pre-mRNA (Parker et al 1987;Wu and Manley 1989;Newman and Norman 1992;Kandels-Lewis and Seraphin 1993;Lesser and Guthrie 1993;Sontheimer and Steitz 1993). Mechanistic and structural similarities between the spliceosomal snRNAs and Group II autocatalytic introns strongly support the hypothesis that spliceosomal snRNA sequences are central to the catalysis of pre-mRNA splicing (Moore and Sharp 1993;Padgett et al 1994;Boulanger et al 1995;Peebles et al 1995;Sigel et al 2000;Villa et al 2002;Hilliker and Staley 2004). In particular an RNA complex between U2 and U6 snRNAs is believed to play a critical role in the catalytic core of the spliceosome, acting as a scaffold to juxtapose the reactive 5¢SS and BP sequences and to position a bound metal ion that is essential for splicing catalysis (Madhani and Guthrie 1992;Sun and Manley 1995;Yean et al 2000;Huppler et al 2002;Sashital et al 2004).…”
Section: Introductionmentioning
confidence: 72%
“…The catalytic core of the spliceosome consists of a highly structured RNA network formed between U2, U6, and U5 snRNAs and the sites of chemistry in the pre-mRNA (Parker et al 1987;Wu and Manley 1989;Newman and Norman 1992;Kandels-Lewis and Seraphin 1993;Lesser and Guthrie 1993;Sontheimer and Steitz 1993). Mechanistic and structural similarities between the spliceosomal snRNAs and Group II autocatalytic introns strongly support the hypothesis that spliceosomal snRNA sequences are central to the catalysis of pre-mRNA splicing (Moore and Sharp 1993;Padgett et al 1994;Boulanger et al 1995;Peebles et al 1995;Sigel et al 2000;Villa et al 2002;Hilliker and Staley 2004). In particular an RNA complex between U2 and U6 snRNAs is believed to play a critical role in the catalytic core of the spliceosome, acting as a scaffold to juxtapose the reactive 5¢SS and BP sequences and to position a bound metal ion that is essential for splicing catalysis (Madhani and Guthrie 1992;Sun and Manley 1995;Yean et al 2000;Huppler et al 2002;Sashital et al 2004).…”
Section: Introductionmentioning
confidence: 72%
“…Indeed, U814 is adjacent to the AGC ''triad'' of D5, which is among the most conserved and catalytically important regions of the intron (Chanfreau and Jacquier 1994;Boulanger et al 1995;Peebles et al 1995;Konforti et al 1998a), and which resembles a similar triad within the spliceosomal U6 snRNA (Madhani and Guthrie 1992;Hilliker and Staley 2004). The conservation and mutational sensitivity of the AGC triad has long led to the expectation that it is a central component of the intron active site.…”
Section: G1: a Novel Role In The First Step Of Splicingmentioning
confidence: 99%
“…Many studies have demonstrated the central importance of nucleotides in D5 (Chanfreau and Jacquier 1994;Peebles et al 1995;Abramovitz et al 1996;Boudvillain et al 2000). A remaining mystery, however, is the role of functionalities in the essential 2-nucleotide (nt) bulge that separates the upper and lower stems of the D5 hairpin.…”
Section: Introductionmentioning
confidence: 99%
“…Domains 5 and 6 (and 1) of yeast group II introns have been shown to be essential for splicing (Jarrell et al, 1988% Boulanger et al, 1995Peebles et al, 1995) and evidence has been obtained supporting the view that an edit in domain 6 of the Oenothera c/d intron is necessary for intron excission (Borner et al, 1995). We generated cDNAs from primers antisense to the exon downstream from each maize nadl intron.…”
Section: Translation Initiation Of Mat-r Transcripts (Alsomentioning
confidence: 73%